Development of polylactide composites with improved thermomechanical properties by simultaneous use of basalt powder and a nucleating agent. Issue 7 (8th April 2020) - Barczewski, Mateusz; Mysiukiewicz, Olga; Matykiewicz, Danuta; Skórczewska, Katarzyna; Lewandowski, Krzysztof; Andrzejewski, Jacek; Piasecki, Adam
Abstract: In the course of the study, polylactide (PLA)/basalt powder (BP) composites were fabricated, incorporating micrometric particle‐shaped waste filler into the biodegradable polyester matrix to obtain improved thermomechanical stability of the final products. The mechanical, thermomechanical, and thermal properties of PLA‐based composites were evaluated, accounting for the influence of the simultaneous incorporation of 1 wt% of the potassium salt of 3, 5‐bis(methoxycarbonyl) benzenesulfonate (LAK) used as the nucleating agent and 5‐20 wt% of basalt powder. As each of the applied modifying agents improves the thermomechanical stability of PLA, a beneficial effect of the co‐modification on thermal properties was expected to widen the temperature range of application of the composites. Differential scanning calorimetry measurements showed an increase of crystallinity up to 55% in the case addition of both additives (BP and LAK) on the PLA. The thermomechanical stability of the composites was determined as a heat deflection temperature (HDT) test. High modification efficiency of BP was obtained only with the simultaneous addition of the LAK nucleating agent. The synergistic effect of both modifiers allowed us to achieve a more than 100% increase in the HDT value to almost 160°C. The mechanical properties were assessed by the static tensile test, Dynstat impact measurements, and a ball indentation hardness evaluation. Even though a 10 MPa decrease in tensile strength was observed due to the addition of 20 wt% of BP and 1% of LAK, the tensile modulus increased from 2.5 to 3.25 MPa and hardness rose from 140 to 175 MPa. The addition of 5 wt% of basalt powder caused a 2 kJ/m 2 increase in impact strength. The modification of PLA with the filler and the nucleating agent improved not only thermal stability but also the mechanical properties of the material.